Investigating the extend of meaning distortion in grade 10 English First Additional Language learners' academic essay writing when they use WhatsApp language - Golele, Thapelo Eugene (My University, 2023)
This study investigated the Grade 10 English First Additional Language (EFAL) learners’ extent of meaning distortion they commit in their academic essay writing due to obsessive exposure to communication in WhatsApp language. This follows the researcher’s observations that most Grade 10 EFAL learners’ essay writing tasks in Kgakotlou Circuit are riddled with informal English register and a range of other language errors associated to the use of WhatsApp language. These include the use of slang, numerous spelling errors, fragmented sentences, and gross grammatical errors. In order to get a better understanding of the problem studied, a qualitative case study research design was employed. Data were successfully gathered from a sample of 4 educators and 22 learners. The participants were purposively selected from the Capricorn District’s rural-based high school. The following data collection tools were used to collect data; participant observation, document analysis, focus-group discussions, and the semi-structured interviews. The collected data helped to address the problem investigated. Data were triangulated and analysed using two data analysis methods, namely; content analysis for observation and the thematic data analysis for the interview and focus-group discussion data sets. This study revealed that the learners’ level of exposure to the WhatsApp language they use for informal communication makes them commit language errors that result in the deformation, omission, and substitution of the key words or phrases that help construct meaning in their academic essays. Secondly, the study established that learners perceive the use of WhatsApp language in academic writing as an effective tool to help them cope with the writing challenges they experience when communicating in English. Learners do not understand the academic writing concept. Thirdly, teachers need better and effective language error-correction strategies since their use of dictation is evidently ineffective to redress the WhatsApp language challenges their learners experience.
Thesis (M.Ed. (Language Education)) -- University of Limpopo, 2023
Keywords: Social media; Meaning distortion; Slang; English first additional language; WhatsApp; English language -- Slang; Social media -- Influence; English language -- Errors of usage